Polyester heat-shrinkable film with easy recycling process

CN122996110APending Publication Date: 2026-10-27SK CHEMICALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480089795.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-18
Filing Date
2024-05-28
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0021]当根据本发明的热收缩膜与PET碎片混合,随后对该混合物进行热处理并离心时,分离率相对于G力的线性回归曲线的斜率被调节到一定范围。结果,与已经通过常规结块测试的热收缩膜相比,可以在各种条件下定量控制可回收性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996110A_ABST
    Figure CN122996110A_ABST
Patent Text Reader

Abstract

A heat shrinkable film in which, when a film chip is mixed with a PET chip and subjected to heat treatment followed by centrifugation, the slope of a linear regression curve of the separation rate with respect to G force is controlled within a certain range, the heat shrinkable film can exhibit excellent recyclability under various conditions, and the recyclability of the film can be quantitatively controlled under a range of conditions compared to a conventional heat shrinkable film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an easily recyclable polyester heat-shrinkable film. Background Technology

[0002] Polyesters, a type of polymer, are used as materials in various fields due to their excellent mechanical strength, heat resistance, transparency, and gas barrier properties. In particular, heat-shrinkable films made from polyester resins have high heat resistance and suitable heat shrinkage rates; therefore, they are suitable for packaging materials and / or labels for plastic containers such as PET bottles.

[0003] Plastic containers have made daily life more convenient; however, due to indiscriminate disposal or overuse, environmental problems have become very serious. Therefore, various methods for recycling waste plastic containers after use are being developed. The processes for recycling waste plastic containers can be divided into physical recycling processes, which involve washing and shredding, and chemical recycling processes, which involve depolymerization.

[0004] However, such a recycling process requires pre-treatment steps to separate waste plastics by type, which reduces the efficiency of the recycling process. For example, to recycle PET bottles labeled with polyester film, the polyester film must be separated and removed from the PET bottle. For containers with film, the container and film are separated at a recycling sorting station for separate container recycling. Without separation, disposal methods such as landfilling are used, causing environmental pollution and significantly reducing resource utilization efficiency.

[0005] In particular, for aesthetic purposes, recycling plastic containers requires the removal of packaging materials and / or labels attached to the containers. Specifically, plastic containers are combined with heat-shrinkable polyester film as packaging material and / or labels. Due to the difference in crystallinity between the polyester film and the plastic container, recycling waste plastic containers requires separating (removing) the polyester film from the waste plastic container, which reduces the recyclability of the waste plastic container.

[0006] Meanwhile, the thermal properties of polyester heat-shrinkable film vary significantly depending on the resin, additives, and processing conditions such as extrusion and stretching. Specifically, the film is heat-shrinked to adhere tightly to the container. For subsequent recycling along with the container, it must be dried and crystallized. Recycling companies perform various heat treatments (temperature, time, etc.), during which the thermal properties change again.

[0007] The agglomeration test from the Association for Plastic Recycling (APR) has been used as a method to assess the recyclability of conventional heat-shrinkable films. This method assesses the degree of fusion by mixing PET fragments and 3% of the film in a hot air oven at 210°C (reduced to 195°C) for 90 minutes. After sieving, unfused or poorly fused samples are separated as they pass through the sieve, and the amount of material remaining on the sieve is measured for evaluation.

[0008] However, in agglomeration tests, there are no clear guidelines for sieving speed, height, etc.; therefore, the results—what remains on the sieve—varie from person to person. This variation is particularly pronounced in samples with low fusion rates. Furthermore, changes in the APR specifications indicate that the agglomeration test conditions are designed for laboratory testing. In actual recycling companies, these conditions are difficult to apply due to variations in heat treatment temperatures and times.

[0009] [Existing Technical Documents]

[0010] [Patent Literature]

[0011] (Patent Document 1) Korean Patent Publication No. 2009-0062882. Summary of the Invention

[0012] Technical issues

[0013] As mentioned above, the thermal properties of polyester film alone cannot predict film deformation, such as fusion or bonding, during heat treatment in the recycling process. The agglomeration test of APR uses an ambiguous screening method, which makes it difficult for those skilled in the art to quantify the strength and extent of fusion, and its disadvantage is that it can only be evaluated under specific temperature (195°C) and time (90 minutes) conditions.

[0014] As a result of research aimed at solving this problem, the inventors mixed membrane fragments with PET fragments, heat-treated them under various heat treatment temperatures and times, and analyzed the degree of separation of the fused samples by centrifugation, thus discovering that recyclability under these conditions could be quantified. Furthermore, the inventors have demonstrated that the membrane is easily recovered under these conditions when the difference between the melt temperature measured after heat treatment and the heat treatment temperature is within a certain range.

[0015] Therefore, the present invention provides a polyester film that can be recycled together with PET containers without separating it from the PET containers, thereby providing a method for reducing environmental pollution and improving resource utilization efficiency. Specifically, an object of the present invention is to provide a heat-shrinkable polyester film whose recyclability is controlled within a specific range by quantitative standards, and whose recycling is easily carried out under various conditions.

[0016] Solution to the problem

[0017] In accordance with the above objectives, the present invention provides a heat-shrinkable film comprising a copolyester resin comprising a diol component and a dicarboxylic acid component, wherein when a mixture is prepared by (i) fragments obtained by cutting the heat-shrinkable film into squares with a side length of 10 mm or less, and (ii) fragments obtained by crushing polyethylene terephthalate (PET) containers to a particle size of 12.5 mm or less, in a weight ratio of 3:97, and when the mixture is heat-treated at a temperature of 140°C to 210°C for 30 to 90 minutes, no fusion product is formed; or, when the fusion product is centrifuged, the slope of a linear regression curve of the following separation rate (%) relative to G force (G) is 0.02% / G or greater.

[0018] Separation rate (%) = [Total weight of fragments separated from the fusion product during centrifugation (g) / Weight of the initial fusion product (g)] × 100.

[0019] Furthermore, the present invention provides a heat-shrinkable film comprising a copolyester resin comprising a diol component and a dicarboxylic acid component, wherein a mixture is prepared by (i) fragments obtained by cutting the heat-shrinkable film into squares with a side length of 10 mm or less, and (ii) fragments obtained by crushing polyethylene terephthalate (PET) containers to a particle size of 12.5 mm or less, at a weight ratio of 3:97, and the mixture is heat-treated at a temperature of 140°C to 210°C for 30 to 90 minutes, while the temperature is increased from 20°C to 280°C at a rate of 10°C / min using differential scanning calorimetry (DSC) during the first scan, the melting temperature (T) is... m It occurs at temperatures 10°C or higher than the heat treatment temperature.

[0020] Beneficial effects of the invention

[0021] When the heat-shrinkable film according to the invention is mixed with PET fragments, and then the mixture is heat-treated and centrifuged, the slope of the linear regression curve of the separation rate relative to G-force is adjusted to a certain range. As a result, recyclability can be quantitatively controlled under various conditions compared to heat-shrinkable films that have passed conventional agglomeration tests.

[0022] Furthermore, when the heat-shrinkable film according to the invention is mixed with PET fragments and then the mixture is heat-treated, the difference between the measured melting temperature and the heat treatment temperature is controlled within a certain range. As a result, it can be easily recycled under various conditions compared to heat-shrinkable films that have passed conventional agglomeration tests. Attached Figure Description

[0023] Figures 1 to 7The graph and linear regression curve show the separation rate versus G-force when the mixture of heat-shrinkable film fragments and PET fragments was heat-treated and centrifuged in Test Example 2. Detailed Implementation

[0024] Best Implementation of the Invention

[0025] In this specification, the terms used to refer to the various components are used to distinguish them from each other and are not intended to limit the scope of the embodiments. Furthermore, in this specification, unless the context otherwise requires, singular expressions are to be construed as also encompassing plural expressions.

[0026] Throughout this specification, the terms "first," "second," etc., are used to describe various components. However, these components should not be limited by these terms. These terms are only used to distinguish one element from another.

[0027] In this specification, the term "comprising" is intended to specify a particular feature, region, step, process, element, and / or component. Unless otherwise expressly stated, the presence or addition of any other feature, region, step, method, element, and / or component is not excluded.

[0028] As is well known, the molecular weights of the compounds or polymers described in this specification, such as number-average molecular weight or weight-average molecular weight, are based on the relative mass of carbon-12. Although their units are not described, they can be understood as molar masses (g / mole) of the same value if necessary.

[0029] Within the numerical ranges of limiting component size and physical properties described in this specification, when examples are given of numerical ranges limited only by the upper limit and numerical ranges limited only by the lower limit, it should be understood that numerical ranges combining these upper and lower limits are also included within the scope of the present invention.

[0030] Fusion properties of heat shrink film

[0031] When a mixture is prepared by (i) fragments obtained by cutting a heat-shrinkable film according to an embodiment of the invention into squares with a side length of 10 mm or less, and (ii) fragments obtained by crushing a polyethylene terephthalate (PET) container to a particle size of 12.5 mm or less, in a weight ratio of 3:97, and the mixture is heat-treated at a temperature of 140°C to 210°C for 30 to 90 minutes, no fusion product is formed; or, when the fusion product is centrifuged, the slope of the linear regression curve of the following separation rate (%) relative to G force (G) is 0.02% / G or greater.

[0032] Separation rate (%) = [total weight of fragments separated from the fusion product during centrifugation (g) / weight of the initial fusion product (g)] × 100.

[0033] The fusion properties of the heat-shrinkable film according to one embodiment can be evaluated by preparing a mixture in a weight ratio of (i) fragments obtained by cutting the heat-shrinkable film into squares with a side length of 10 mm or less, and (ii) fragments obtained by crushing polyethylene terephthalate (PET) containers to a particle size of 12.5 mm or less, in a ratio of 3:97, and by heat-treating the mixture at a temperature of 140°C to 210°C for 30 to 90 minutes, and confirming whether a fusion product is formed. When a fusion product is formed, the fusion product is centrifuged, and it is confirmed that the slope of the linear regression curve of the separation rate (%) versus G force (G) is 0.02% / G or greater.

[0034] First, the heat-shrinkable polyester film is cut into squares with sides of 10 mm or less to obtain fragments (film fragments). Additionally, the polyethylene terephthalate (PET) container is pulverized to a particle size of 12.5 mm or smaller to obtain fragments (PET fragments). For example, the PET container is pulverized in a pulverizer and passed through a sieve with a mesh diameter of 12.5 mm to obtain fragments. A mixture of these fragments (film fragments and PET fragments) is then obtained.

[0035] The mixture of fragments is subjected to heat treatment. The heat treatment of the mixture of fragments can be carried out using, for example, a convection oven or a hot air tunnel.

[0036] The heat treatment temperature of the fragment mixture can be, for example, 140°C or higher, 150°C or higher, 160°C or higher, or 170°C or higher, and 210°C or lower, 200°C or lower, 190°C or lower, or 180°C or lower. According to one embodiment, the heat treatment temperature of the fragment mixture is 140°C to 210°C. More specifically, the heat treatment temperature of the fragment mixture can be 150°C to 200°C.

[0037] The heat treatment time for the mixture of fragments can be, for example, 30 minutes or longer, 40 minutes or longer, 50 minutes or longer, or 60 minutes or longer, and 90 minutes or less, 80 minutes or less, or 70 minutes or less. According to one embodiment, the heat treatment time for the mixture of fragments is 30 to 90 minutes.

[0038] Check for the formation of any fusion products after heat treatment. After heat treatment, the film fragments can retain their shape without completely melting.

[0039] According to one implementation scheme, the membrane fragments may not fuse with the PET fragments after heat treatment.

[0040] According to another embodiment, after heat treatment, the membrane fragments can form a partial fusion product with the PET fragments. Whether a fusion product has formed between the membrane fragments and the PET fragments can be determined by visual observation.

[0041] The size of the fused product can be at a certain level or smaller. For example, the size of the fused product of film fragments and PET fragments formed after heat treatment cannot exceed twice the size of the PET fragments. As another example, the size of the fused product of film fragments and PET fragments formed after heat treatment cannot exceed 1.5 times the size of the PET fragments.

[0042] As mentioned above, after heat treatment of the fragment mixture, a fusion product may not be formed, or a fusion product with a particle size not exceeding twice the particle size of the PET container fragments may be formed.

[0043] The fusion product formed after heat treatment is centrifuged. For example, centrifugation can be carried out at a force of 100G to 650G.

[0044] Specifically, a certain amount (e.g., 3 g) of the fusion product can be taken, filled to 25% or less in a conical tube, mounted on a centrifuge, and centrifuged at a predetermined G-force value for 1 minute. After centrifugation, the fragments separated from the fusion product are collected and their weight is measured. Whether they are fragments separated from the fusion product can be determined by visual observation. The separation rate (%) is then calculated according to the equation described above. This step is performed at different G-forces to obtain the separation rate (%) at each G-force. For example, five or more centrifugations can be performed at different G-forces ranging from 100 G to 650 G to collect data.

[0045] Regression analysis is performed to simulate the linear correlation of the data collected in this way, with Gforce (G) as the independent variable x and the separation rate (%) as the dependent variable y, including the intercept. The slope of the linear regression curve is obtained through regression analysis.

[0046] According to one implementation scheme, the slope of the linear regression curve is 0.02% / G or greater. Within this range, it can be determined that the recycling process between heat-shrinkable polyester film and PET subjected to the above conditions is excellent.

[0047] For example, the slope of the linear regression curve can be 0.02% / G or greater, 0.025% / G or greater, 0.03% / G or greater, or 0.035% / G or greater.

[0048] Meanwhile, there is no particular upper limit to the slope of the linear regression curve. However, it can be, for example, 1 or less, 0.9 or less, 0.7 or less, 0.5 or less, 0.3 or less, 0.1 or less, 0.07 or less, or 0.05 or less.

[0049] As a specific example, the slope of the linear regression curve can be 0.02% / G to 1% / G, 0.02% / G to 0.3% / G, 0.02% / G to 0.1% / G, or 0.02% / G to 0.05% / G.

[0050] Thermal properties of heat shrink film

[0051] Polyethylene terephthalate (PET), composed of terephthalic acid (TPA) and ethylene glycol (EG), has a regular molecular arrangement and is highly crystalline. When stretched, heat shrinkage is suppressed due to the additional increase in crystallinity caused by stretching orientation; therefore, it is difficult to use as a heat-shrinkable film requiring high shrinkage rates. For this reason, other comonomers such as cyclohexanediol (CHDM), neopentyl glycol (NPG), diethylene glycol (DEG), and 1,4-butanediol (1,4-BD) are used for heat-shrinkable films. With increasing comonomer content, crystallinity decreases and amorphousness increases; therefore, high shrinkage rates can be obtained. Generally, with increasing comonomer content, the melting temperature (T0) increases. m ) decreases, and at the melting temperature (T m The ΔH also decreases under these conditions, confirming a decrease in crystallinity. Furthermore, resins with a certain amount or more of comonomers may become amorphous, where the melting temperature (T0) is not observed in DSC measurements. m ).

[0052] However, polymers cannot be 100% crystalline or 100% amorphous; rather, both exist, and their proportions vary depending on the content of the comonomer. In particular, when stretched, there is no melting temperature (T0). m When using amorphous resins, a small number of crystalline regions may appear depending on the stretching orientation. Therefore, even with a melting temperature (T... m It does not appear in the resin, and its melting temperature (T) m It may also appear in stretch membranes.

[0053] Heat shrink films with high shrinkage rates are composed of resin compositions having a high amorphous region. Therefore, even if a melting temperature (T0) does not occur in the resin... m ) or very weakly, due to stretching orientation, melting temperature (T) can also be observed in stretched films. m Therefore, only the melting temperature (T) of the resin or stretched film... mThe temperature and time at which the film actually does not melt cannot be determined. This is because, at certain temperatures, stretched and oriented crystals may grow larger to increase T. m And ΔH; however, at other temperatures, the crystals that have already formed may also melt.

[0054] Therefore, the melting temperature (T) of ordinary films m The feasibility of a recycling process under specific heat treatment conditions cannot be determined by a single factor; rather, the melting temperature (T) of the film after heat treatment under certain conditions is a crucial factor. m This is important. Therefore, it can be checked by examining the melt temperature (T) after heat-treating the mixture of film fragments and PET fragments. m The specific methods and conditions for preparing and heat-treating the mixture of fragments can be those exemplified above in the description of the recyclability of heat-shrinkable films.

[0055] To measure the melting temperature of a membrane, a differential scanning calorimeter (DSC) can be used. Specifically, a modulated differential scanning calorimeter (modulated DSC or MDSC) can be used, and more specifically, a temperature-modulated differential scanning calorimeter (temperature-modulated DSC or TMDSC) can be used. For example, when the temperature rises from room temperature (e.g., 20 °C) to 280 °C at a rate of 10 °C / min, the melting temperature of the membrane can be measured by scanning with a differential scanning calorimeter (DSC).

[0056] In a heat-shrinkable film according to one embodiment, a mixture is prepared by combining (i) fragments obtained by cutting the heat-shrinkable film into squares with a side length of 10 mm or less, and (ii) fragments obtained by crushing polyethylene terephthalate (PET) containers to a particle size of 12.5 mm or less, at a weight ratio of 3:97. This mixture is then heat-treated at a temperature of 140°C to 210°C for 30 to 90 minutes, and the temperature is increased from 20°C to 280°C at a rate of 10°C / min using differential scanning calorimetry (DSC) during the first scan. The melting temperature (T) is... m It occurs at temperatures 10°C or higher than the heat treatment temperature.

[0057] In other words, the value obtained by subtracting the melting temperature (°C) from the heat treatment temperature (°C) of the film can be 10°C or lower. Within the above preferred range, it can be determined that the recycling process between the polyester heat-shrinkable film and PET subjected to the above heat treatment conditions is excellent.

[0058] Therefore, a mixture was prepared by combining (i) fragments obtained by cutting heat-shrinkable film into squares with sides of 10 mm or less, and (ii) fragments obtained by crushing polyethylene terephthalate (PET) containers to a particle size of 12.5 mm or less, at a weight ratio of 3:97. This mixture was then heat-treated at 140°C to 210°C for 30 to 90 minutes, with a first scan performed using differential scanning calorimetry (DSC) while the temperature was increased from 20°C to 280°C at a rate of 10°C / min. The melting temperature (T0) was then observed. m To assess the recyclability of the heat-shrinkable film, we can determine whether it occurs at a temperature 10°C or higher than the heat treatment temperature (i.e., a temperature equal to or higher than 10°C below the heat treatment temperature).

[0059] In addition, the melting temperature (T) m This occurs at temperatures 5°C or higher than the heat treatment temperature. In other words, the value obtained by subtracting the melting temperature (°C) from the heat treatment temperature (°C) of the film can be 5°C or lower.

[0060] More specifically, melting temperature (T m This occurs at temperatures equal to or higher than the heat treatment temperature. In other words, the value obtained by subtracting the melting temperature (°C) from the heat treatment temperature (°C) of the film can be 0°C or lower.

[0061] After the heat treatment of the heat-shrinkable film, one, two, or more melting temperatures (T) may appear in the first DSC scan. m If there are two or more, the higher temperature can be considered the melting temperature (T). m ).

[0062] Furthermore, in the first DSC scan after heat treatment, at the melting temperature (T) m The enthalpy of fusion (ΔH) at the melting temperature can be at a certain level or higher. For example, in the first scan, the enthalpy of fusion at the melting temperature (T) can be at a certain level or higher. m The ΔH at the melting temperature (T) can be 0.1 J / g or greater. Specifically, in the first scan, the ΔH at the melting temperature (T) m The ΔH at the melting temperature (T) can be 0.5 J / g or greater, 1 J / g or greater, 2 J / g or greater, 3 J / g or greater, 5 J / g or greater, 7 J / g or greater, or 10 J / g or greater. More specifically, in the first scan at the melting temperature (T) mThe ΔH at the specified temperature can be 0.1 J / g to 100 J / g, 0.1 J / g to 50 J / g, 0.1 J / g to 30 J / g, 0.5 J / g to 100 J / g, 0.5 J / g to 50 J / g, 0.5 J / g to 30 J / g, or 0.5 J / g to 20 J / g. Even after heat treatment within the above preferred ranges, a melting temperature (T0) still exists. m The values ​​of enthalpy of fusion (ΔH) indicate that the membrane fragments were not completely melted at the heat treatment temperature and time, and therefore would not fuse with the PET fragments; or, even if they were fused, they were easily separated, which can be quantitatively confirmed.

[0063] However, after the fragment mixture has been heat-treated and subjected to its first DSC scan, the melting temperature (T) m The melt temperature may not appear in the second scan. Since all the thermal history of the membrane production process is removed after the first scan, the melt temperature obtained from the second scan can be regarded as the melt temperature of the copolyester resin used as the membrane raw material.

[0064] Specifically, when using differential scanning calorimetry (DSC) to raise the temperature from 20°C to 280°C at a rate of 10°C / min while performing a second scan, the melting temperature (T) may not be observed. m As mentioned above, when no melting temperature is reached during the second scan, the low crystallinity of the film provides an advantage in achieving a high shrinkage rate.

[0065] The heat shrink film according to the present invention has excellent shrinkage characteristics at the temperature used in the heat shrink process.

[0066] Under conditions of 85°C and 15 seconds, the heat shrink film can have a shrinkage rate of 40% or higher in the main shrinkage direction. For example, under conditions of 85°C and 15 seconds, the heat shrinkage rate of the heat shrink film in the main shrinkage direction can be 42% or higher, 44% or higher, 46% or higher, 48% or higher, 50% or higher, 52% or higher, 55% or higher, or 60% or higher. Specifically, the heat shrinkage rate of the heat shrink film in the main shrinkage direction can be 40% to 80% or 40% to 75%.

[0067] Furthermore, under conditions of 95°C and 15 seconds, the heat shrink film can have a shrinkage rate of 50% or higher in the main shrinkage direction. For example, under conditions of 95°C and 15 seconds, the heat shrinkage rate of the heat shrink film in the main shrinkage direction can be 51% or higher, 52% or higher, 54% or higher, 56% or higher, 60% or higher, 63% or higher, 65% or higher, or 70% or higher. As a specific example, under conditions of 95°C and 15 seconds, the heat shrink film can have a shrinkage rate of 60% or higher in the main shrinkage direction. Specifically, the heat shrinkage rate of the heat shrink film in the main shrinkage direction can be 50% to 80% or 60% to 80%.

[0068] Therefore, the heat shrink film of the present invention can be used as a label or sealing cap for various plastic containers, and can also be used as packaging material.

[0069] Components of heat shrink film

[0070] The heat-shrinkable film according to the present invention comprises a copolyester resin, which comprises a diol component and a dicarboxylic acid component.

[0071] According to the present invention, the diol component can be a known diol component.

[0072] Specifically, the diol component may be at least one selected from the group consisting of: bis(2-hydroxyethyl) terephthalate (BHET), isosorbide, neopentyl glycol, ethylene glycol, cyclohexanediol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2-methylene-1,3-propanediol, 2-ethyl-1,3-propanediol, 2-isopropyl-1,3-propanediol, 2,2-Dimethyl-1,3-propanediol, 1,4-butanediol, 2,3-butanediol, 3-methyl-1,5-pentanediol, 3-methyl-2,4-pentanediol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,4-cyclohexanediol, diethylene glycol, 4-(hydroxymethyl)cyclohexylmethyl-4-(hydroxymethyl)cyclohexanecarboxylate, and 4-(4-(hydroxymethyl)cyclohexylmethoxymethyl)cyclohexylethanol.

[0073] Preferably, when considering the crystallinity, heat shrinkage, and economic benefits of the heat-shrinkable polyester film, the diol component may include two or more (specifically, three or more, four or more, or five or more) selected from the group consisting of: bis(2-hydroxyethyl) terephthalate, isosorbide, ethylene glycol, cyclohexanediol, neopentyl glycol, diethylene glycol, 4-(hydroxymethyl)cyclohexylmethyl-4-(hydroxymethyl)cyclohexanecarboxylate, and 4-(4-(hydroxymethyl)cyclohexylmethoxymethyl)cyclohexylethanol.

[0074] For example, the diol component may include ethylene glycol and at least one selected from the group consisting of (specifically, two or more, three or more, or four or more): bis(2-hydroxyethyl) terephthalate, isosorbide, cyclohexanediol, neopentyl glycol, diethylene glycol, 4-(hydroxymethyl)cyclohexylmethyl-4-(hydroxymethyl)cyclohexanecarboxylate and 4-(4-(hydroxymethyl)cyclohexylmethoxymethyl)cyclohexylethanol as comonomers.

[0075] When the glycol component contains ethylene glycol and comonomer, there are no particular restrictions on the amount of these components used. However, based on the total weight of the glycol component, the amount of ethylene glycol can be 10% by weight to less than 100% by weight, 15% by weight to 90% by weight, 20% by weight to 85% by weight, 30% by weight to 85% by weight, or 50% by weight to 85% by weight, and the amount of comonomer can be greater than 0% by weight to 90% by weight, greater than 0% by weight to 85% by weight, 1% by weight to 90% by weight, 1% by weight to 50% by weight, 2% by weight to 50% by weight, 10% by weight to 85% by weight, 15% by weight to 80% by weight, 15% by weight to 70% by weight, or 15% by weight to 50% by weight.

[0076] In particular, when diethylene glycol is used as a comonomer, the amount of diethylene glycol used can be 0% to 50% by weight, 1% to 50% by weight, 1% to 45% by weight, 1% to 40% by weight, 2% to 50% by weight, 3% to 45% by weight, 4% to 40% by weight, or 5% to 35% by weight, based on the total weight of the diethylene glycol component.

[0077] Therefore, based on the total weight of the polyester resin, the polyester resin according to the present invention may contain 0% to 50% by weight, 1% to 50% by weight, 2% to 50% by weight, 3% to 45% by weight, 4% to 40% by weight, or 5% to 35% by weight of diethylene glycol-derived structural units.

[0078] According to the present invention, the dicarboxylic acid component can be a common dicarboxylic acid component.

[0079] Specifically, the dicarboxylic acid component may include at least one selected from the group consisting of: isophthalic acid, terephthalic acid, dimethyl isophthalate, phthalic acid, dimethyl phthalate, phthalic anhydride, 2,6-naphthalenedicarboxylic acid, dimethyl 2,6-naphthalenedicarboxylic acid, diphenyl dicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, dimethyl 1,4-cyclohexanedicarboxylic acid, dimethyl 1,3-cyclohexanedicarboxylic acid, sebacic acid, succinic acid, isodecylsuccinic acid, maleic acid, maleic anhydride, fumaric acid, adipic acid, glutaric acid, and azelaic acid.

[0080] Preferably, when considering the crystallinity and heat shrinkage of the stretched polyester film, the dicarboxylic acid component may include at least one selected from the group consisting of isophthalic acid, terephthalic acid, dimethyl phthalate and dimethyl isophthalate.

[0081] The diol and dicarboxylic acid components may contain one or more types of recycled monomers.

[0082] For example, the glycol component may contain recycled monomers obtained through the depolymerization of waste polyester. As a specific example, the glycol component may include at least one recycled monomer selected from the group consisting of recycled glycols and recycled glycol derivatives. As a more specific example, the glycol component may include at least one recycled monomer selected from the group consisting of recycled bis(2-hydroxyethyl) terephthalate, recycled ethylene glycol, recycled 1,4-cyclohexanediol, recycled neopentyl glycol, recycled diethylene glycol, and recycled isosorbide, but is not limited thereto.

[0083] As another example, the dicarboxylic acid component may include recycled monomers obtained through the depolymerization of waste polyester. As a specific example, the dicarboxylic acid component may include at least one recycled monomer selected from the group consisting of recycled dicarboxylic acids and recycled dicarboxylic acid derivatives. As a more specific example, the dicarboxylic acid component may include, but is not limited to, at least one recycled monomer selected from the group consisting of recycled isophthalic acid, recycled terephthalic acid, recycled dimethyl isophthalate, and recycled dimethyl phthalate.

[0084] As mentioned above, the recycled monomers obtained through the depolymerization of waste polyester need to be understood as different from virgin or pure monomers. Specifically, recycled monomers may contain reagents or solvents used in various chemical steps during the depolymerization process of waste polyester, or byproducts formed from their side reactions. Therefore, in addition to monomer compounds as the main components, monomers recovered through ordinary depolymerization processes also contain organic and inorganic impurities; thus, their purity is not high. For this reason, recycled monomers can also be considered as a composition containing two or more components.

[0085] According to the present invention, the polyester resin can have an intrinsic viscosity (IV) of 0.5 dl / g to 1.2 dl / g or 0.4 dl / g to 1.2 dl / g at 35°C, specifically 0.52 dl / g to 1.15 dl / g, 0.55 dl / g to 1.13 dl / g, 0.58 dl / g to 1.1 dl / g, 0.6 dl / g to 0.9 dl / g, 0.62 dl / g to 0.88 dl / g, 0.65 dl / g to 0.85 dl / g, 0.68 dl / g to 0.83 dl / g, or 0.7 dl / g to 0.8 dl / g. When the intrinsic viscosity is within the above range, the processability of the polyester resin can be guaranteed.

[0086] Preparation method of heat shrink film

[0087] The method for preparing the heat-shrinkable film according to the present invention may include polymerizing a diol component and a dicarboxylic acid component to prepare a polyester resin (S-1); and preparing a stretch film from the polyester resin (S-2).

[0088] In step (S-1), the diol component and the dicarboxylic acid component are polymerized to prepare a polyester resin (polymer). Since the diol component and dicarboxylic acid component used for polymerization are the same as those described above, their description is omitted.

[0089] The polymerization of diol and dicarboxylic acid components can be carried out by conventionally known methods (e.g., liquid-phase polymerization, solid-phase polymerization, etc.). Batch or continuous reactors can be used for the polymerization reaction. Specifically, the polymerization reaction may include esterification (transesterification) reactions to prepare oligomers by reacting diol and dicarboxylic acid components, and polycondensation reactions of oligomers.

[0090] There are no particular limitations on the temperature for the esterification reaction, but considering the physical properties of the polyester resin and the stretched polyester film, the temperature can be 230°C to 270°C, 235°C to 268°C, 240°C to 265°C, or 240°C to 260°C. Furthermore, there are no particular limitations on the time for the esterification reaction, but it can be 1 hour to 24 hours, 2 hours to 22 hours, 3 hours to 20 hours, or 4 hours to 18 hours. Additionally, there are no particular limitations on the pressure for the esterification reaction, but it can be 0 kgf / cm². 2 Up to 5.0 kgf / cm 2 0.1 kgf / cm 2 Up to 4.5 kgf / cm 2 0.1 kgf / cm 2 Up to 4.0 kgf / cm 2 Or 0.1 kgf / cm 2 Up to 3.0 kgf / cm 2 .

[0091] There are no particular limitations on the temperature for the polycondensation reaction, but considering the physical properties of the polyester resin and the stretched polyester film, the temperature can be 245°C to 290°C, 250°C to 285°C, 255°C to 280°C, or 255°C to 270°C. Furthermore, there are no particular limitations on the time for the polycondensation reaction, but it can be 1 hour to 24 hours, 2 hours to 24 hours, 5 hours to 22 hours, or 7 hours to 20 hours.

[0092] Meanwhile, additives may be used in the polymerization reaction, including at least one selected from the group consisting of catalysts, stabilizers, colorants, crystallizers, antioxidants and branching agents.

[0093] For example, the copolyester resin may include at least one selected from the group consisting of antimony (Sb), titanium (Ti), zinc (Zn), germanium (Ge), magnesium (Mg), and manganese (Mn) as a polymerization catalyst. As a specific example, the catalyst may be tetraethyl titanate, triacetyl titanate, tetrapropyl titanate, tetrabutyl titanate, 2-ethylhexyl titanate, octyl glycol titanate, triethanolamine titanate, acetylacetone titanate, ethyl acetoacetate titanate, isostearyl titanate, titanium dioxide, germanium dioxide, germanium tetrachloride, germanium glycol, germanium acetate, or combinations thereof.

[0094] There are no particular restrictions on stabilizers, but phosphorus-based compounds such as phosphoric acid, trimethyl phosphate, and triethyl phosphate can be used.

[0095] There are no particular restrictions on colorants, but organic compounds such as cobalt-based compounds, anthraquinone-based compounds, perylene-based compounds, azo compounds, and methine compounds (e.g., cobalt acetate, cobalt propionate, blue toners, and red toners) can be used.

[0096] There are no particular restrictions on crystallizing agents, but crystal nucleating agents, ultraviolet absorbers, polyolefin resins, polyamide resins, etc., can be used.

[0097] There are no particular restrictions on antioxidants, but hindered phenolic compounds, phosphite compounds, thioether compounds, etc., can be used.

[0098] There are no particular restrictions on branching agents, but trimellitic anhydride, trimethylolpropane, trimellitic acid, etc. can be used.

[0099] In step (S-2), a stretched film is prepared from the polyester resin obtained in step (S-1). The stretched film can be prepared using conventional methods. For example, a film containing a copolyester resin can be prepared by the following steps: molding the polyester resin mixture to prepare an unstretched sheet; and stretching the unstretched sheet. Specifically, the stretched film can be prepared by a polyester resin melting and molding (casting) step, a uniaxial or biaxial stretching step, etc.

[0100] The melt extrusion and molding steps of the polyester resin can be carried out using an extruder. Here, the melt extrusion temperature can be, for example, 180°C or higher, 200°C or higher, 230°C or higher, 250°C or higher, 255°C or higher, or 260°C or higher, and 310°C or lower, 300°C or lower, 290°C or lower, or 280°C or lower, specifically 180°C to 310°C, 200°C to 310°C, 230°C to 310°C, or 240°C to 300°C. Preferably, the melt extrusion temperature can be 255°C or higher, for example 255°C to 310°C, 255°C to 300°C, or 255°C to 290°C. When the melt extrusion temperature is within the above preferred ranges, the molecular weight and crystallinity of the polyester resin are improved. As a result, the heat-shrinkable film thus prepared is easily recyclable under various conditions and is also advantageous in terms of quantitative control of recyclability.

[0101] Furthermore, the molding temperature can be, for example, 15°C to 60°C or 15°C to 45°C. This process yields an unstretched sheet, which can then be transferred to a stretching step. Prior to the stretching step, the unstretched sheet can be preheated to a predetermined temperature (e.g., 80°C to 120°C).

[0102] The uniaxial or biaxial stretching step may include stretching an unstretched sheet obtained through the melting and molding steps in the longitudinal (MD), transverse (TD) direction, or both. Longitudinal stretching may be performed at temperatures of 55°C to 180°C, 60°C to 130°C, 60°C to 120°C, or 65°C to 90°C at stretch ratios of 1 to 6 times, 1 to 5.5 times, 1 to 5 times, 1.05 to 6 times, 1.1 to 6 times, 1.1 to 5.5 times, 1.1 to 5 times, 1.1 to 4.5 times, or 1.2 to 5.5 times. Furthermore, transverse stretching can be performed at stretching temperatures of 55°C to 180°C, 60°C to 130°C, or 65°C to 90°C, at stretching ratios of 1.1 times or greater, 1.5 times or greater, 2.5 times or greater, 3.5 times or greater, or 4 times or greater, and 6 times or less, 5.5 times or less, or 5 times or less, specifically, 1.5 times to 6 times or 2.5 times to 5.5 times.

[0103] In one embodiment, the film comprising the copolyester resin can be uniaxially stretched at a stretch ratio of 1.5 to 6 times in the transverse direction or at a stretch ratio of 1.05 to 6 times in the longitudinal direction. In another embodiment, the film comprising the copolyester resin can be biaxially stretched at a stretch ratio of 1.5 to 6 times in the transverse direction and at a stretch ratio of 1.05 to 6 times in the longitudinal direction.

[0104] Stretch films can also undergo an additional heat-setting step. There are no particular limitations on the heat-setting temperature of the stretch film, but it can be similar to or higher than the temperature of the stretching step. Specifically, the heat-setting temperature can be 60°C to 200°C, 65°C to 190°C, 65°C to 180°C, or 65°C to 170°C. When the heat-setting temperature is within the above range, a stretch polyester film with high crystallinity and high mechanical strength can be prepared.

[0105] The thickness of the heat-shrinkable film thus prepared can be, for example, 10 μm or greater, 15 μm or greater, 25 μm or greater, 35 μm or greater, or 50 μm or greater, and can be 500 μm or less, 300 μm or less, 200 μm or less, or 100 μm or less. As a specific example, the thickness of the heat-shrinkable film can be from 10 μm to 100 μm.

[0106] A membrane containing copolyester resin can consist of one or more layers. As an example, a membrane containing copolyester resin can be a single-layer membrane. As another example, a membrane containing copolyester resin can be a multilayer membrane consisting of two or more layers. As a specific example, a membrane containing copolyester resin can be a multilayer membrane comprising a base layer and a resin layer. In this case, at least one of the base layer and the resin layer may comprise copolyester resin.

[0107] Implementation of the invention

[0108] [Example]

[0109] In the following description, preferred embodiments are given for the purpose of understanding the invention. However, the following embodiments are provided merely to facilitate a clear understanding of the invention, and the scope of the invention is not limited thereto.

[0110] <Preparation of Copolyester Resin>

[0111] Preparation Example: Resin 1

[0112] A reactor equipped with a column and a water-cooled condenser was charged with 2,950 g of terephthalic acid (TPA), 410 g of ethylene glycol (EG), 970 g of diethylene glycol (DEG), 1,180 g of 1,4-cyclohexanediethanol (CHDM), and 1,130 g of bis(2-hydroxyethyl) terephthalate (BHET) obtained by depolymerization of recycled PET. Then, based on the weight of the monomer mixture, 20 ppm of Ti catalyst and 70 ppm of phosphorus-based stabilizer were added. Next, the reactor temperature was raised to 260 °C, and then... 2 Esterification is carried out under pressure to obtain a transparent material.

[0113] The resulting material was then transferred to a polycondensation reactor and subjected to a polycondensation reaction (PA) at 265°C while maintaining the pressure in the polycondensation reactor below normal. When the intrinsic viscosity (IV) of the mixture in the polycondensation reactor reached 0.65 to 0.75 dl / g, the mixture was then discharged outside the polycondensation reactor to form strips, which were solidified with a coolant and then granulated to an average weight of approximately 15 mg to prepare polyester resin (copolymer) chips.

[0114] Preparation Example: Resin 2

[0115] 3,861 g of terephthalic acid (TPA), 1,605 g of ethylene glycol (EG), 435 g of diethylene glycol (DEG) and 705 g of recovered 1,4-cyclohexanediethanol (CHDM) were charged into a reactor equipped with a column and a water-coolable condenser, and polyester resin (copolymer) chips were prepared in the same manner as resin 1 above.

[0116] Preparation Example: Resin 3

[0117] 3,952 g of terephthalic acid (TPA), 1,755 g of recovered ethylene glycol (EG), 386 g of diethylene glycol (DEG), and 541 g of 1,4-cyclohexanediethanol (CHDM) were charged into a reactor equipped with a column and a water-coolable condenser, and polyester resin (copolymer) chips were prepared in the same manner as resin 1 described above.

[0118] Preparation Example: Resin 4

[0119] 4,131 g of recovered terephthalic acid (TPA), 2,224 g of ethylene glycol (EG), 155 g of diethylene glycol (DEG) and 518 g of neopentyl glycol (NPG) were charged into a reactor equipped with a column and a water-cooled condenser, and polyester resin (copolymer) chips were prepared in the same manner as resin 1 described above.

[0120] Preparation Example: Resin 5

[0121] 4,044 g of terephthalic acid (TPA), 1,672 g of ethylene glycol (EG), 46 g of diethylene glycol (DEG) and 950 g of neopentyl glycol (NPG) were charged into a reactor equipped with a column and a water-cooled condenser, and polyester resin (copolymer) chips were prepared in the same manner as resin 1 described above.

[0122] Preparation Example: Resin 6

[0123] 4,055 g of terephthalic acid (TPA), 1,709 g of ethylene glycol (EG), 152 g of diethylene glycol (DEG) and 794 g of neopentyl glycol (NPG) were loaded into a reactor equipped with a column and a water-cooled condenser, and polyester resin (copolymer) chips were prepared in the same manner as resin 1 described above.

[0124] <Preparation of heat shrink film>

[0125] Example 1

[0126] The polyester resin chips (resins 1 to 6) prepared in the preparation examples were fed into an extruder (Teach-Line from Collin), melt-extruded at 255°C, and molded at 35°C to prepare unstretched polyester sheets. Subsequently, the unstretched sheets were stretched 4.5 times in the transverse (TD) direction only at 78°C, and then air-cooled to prepare stretched polyester films with a thickness of 50 μm.

[0127] Examples 2 to 9

[0128] Except for changing the type of polyester resin chips and process conditions as shown in Table 1 below, each heat shrink film was prepared in the same manner as in Example 1.

[0129] Comparative Examples 1 to 6

[0130] Except for changing the type of polyester resin chips and process conditions as shown in Table 2 below, each heat shrink film was prepared in the same manner as in Example 1.

[0131] [Table 1]

[0132] [Table 2]

[0133] [Test Example]

[0134] Test Example 1: Fusion Evaluation

[0135] (1) Heat treatment

[0136] The heat-shrinkable films prepared in the examples and comparative examples were mixed with PET fragments and heat-treated. First, each polyester heat-shrinkable film was cut into squares with sides of 10 mm or less to obtain film fragments. Additionally, polyethylene terephthalate (PET) containers were pulverized in a pulverizer and passed through a 12.5 mm mesh to prepare PET fragments, wherein the polyethylene terephthalate (PET) was pulverized. The film fragments and PET fragments were mixed at a weight ratio of 3:97 and then heat-treated under the conditions shown in Tables 3 and 4 below.

[0137] [Table 3]

[0138] [Table 4]

[0139] (2) Fusion assessment

[0140] Check whether any fusion product has formed after the heat treatment in step (1) above. If a fusion product is formed, mark it as "fused" in Table 5 or 6 below.

[0141] In addition, when the fused product is formed, the size (particle diameter) of the fused product is measured, and the ratio of the fused product size to the PET fragment size is shown in Table 5 or 6 below (i.e., if it is twice or less than the PET fragment size, it is indicated as “≤2”; if it is more than twice the PET fragment size, it is indicated as ">2”).

[0142] Furthermore, if the shape of the film is not maintained after the heat treatment in step (1) above and is fused, it is marked as “fused” in Table 5 or 6 below.

[0143] (3) Centrifugation

[0144] Take 3 g of the fusion product of the membrane fragments and PET fragments formed by heat treatment in step (1), fill a conical tube to 25% or less, mount it on a centrifuge, reach a predetermined G-force value, and hold for 1 minute. As a result, collect the fragments separated from the fusion product and measure their weight. The separation rate (%) is calculated according to the equation below. The process is carried out at various G-forces from 100 G to 650 G to obtain the separation rate (%).

[0145] Separation rate (%) = [total weight of fragments separated from the fusion product during centrifugation (g) / weight of the initial fusion product (g)] × 100.

[0146] (4) Regression Analysis

[0147] Using the separation rate (%) obtained at each G force, a regression analysis was performed on the separation rate (%) relative to the G force. The slope and intercept of the linear regression curve were obtained as a result.

[0148] Figures 1 to 7 The graph shows the slope and y-intercept of the linear regression curve with G force as the x-axis and separation rate (%) as the y-axis.

[0149] Test Example 2: DSC Analysis

[0150] (1) Film T before heat treatment mMeasurement (DSC) - First Scan

[0151] Each heat-shrinkable film prepared in the examples and comparative examples was analyzed by differential scanning calorimetry (DSC) to measure the melting temperature (T). m The conditions for DSC analysis are as follows.

[0152] DSC analysis device: Mettler Toledo DSC 1 model.

[0153] Sample preparation: Take about 6-10 mg of each type of heat shrink film and place it in an aluminum tray.

[0154] Scanning conditions: Heat from 20°C to 280°C at a rate of 10°C / min, followed by annealing at 280°C for 3 minutes to obtain DSC curves.

[0155] (2) T of the film after heat treatment (DSC) m Measurement - First Scan

[0156] The heat-shrinkable films prepared in the examples and comparative examples were each cut and mixed with PET fragments at a weight ratio of 3:97, and heat-treated in the same manner as step (1) of Test Example 1. Subsequently, under the same conditions as part (1) of Test Example 2, a first scan of the heat-treated film was performed using DSC to measure the melting temperature. Specifically, the final endothermic peak temperature (i.e., the highest endothermic peak temperature) during the heating process in the obtained DSC curve was taken as the melting temperature (of the heat-treated film) in the first scan. When the melting temperature is measured in the first scan after heat treatment, it is shown in Table 5 or 6 below.

[0157] (3) Membrane T m Measurement (DSC) - Second Scan

[0158] The heat-shrinkable film that underwent the first scan in Part (2) of Test Example 2 was quenched and then scanned again by DSC under the same conditions as the first scan (second scan) to measure the melting temperature. When the melting temperature is measured in the second scan, it is shown in Table 5 or 6 below. Since all the thermal history of the film production process is removed after the first scan, the melting temperature obtained from the second scan can be regarded as the melting temperature of the polyester resin.

[0159] Test Example 3: Heat Shrinkage Rate

[0160] Each heat-shrinkable film prepared in the examples and comparative examples was cut into 5 cm × 5 cm pieces and stored at room temperature (20°C). Each film was immersed in hot water at 95°C for 15 seconds, and its length change in the transverse direction (TD), which is the main shrinkage direction, was measured. The heat shrinkage rate was calculated using the following equation.

[0161] Heat shrinkage rate (%) = {(F S1 –F S2 ) / F S1}×100

[0162] (F S1 : The TD length of the membrane before immersion in hot water, and F S2 (TD length of the membrane after immersion in hot water)

[0163] The test results are shown in the table below.

[0164] [Table 5]

[0165] [Table 6]

[0166] As can be seen from the table above, in the heat shrink films of Examples 1-9, no fusion product was formed after mixing with PET fragments and heat treatment; or even if a fusion product was formed, the slope of the linear regression curve of the separation rate relative to the G force was within the expected range. Furthermore, in the heat shrink films of Examples 1 to 9, the melting temperature measured after mixing with PET fragments and heat treatment fell within the expected range.

[0167] Conversely, in the heat-shrinkable films of Comparative Examples 1 to 6, a fused product was formed after mixing with PET fragments and heat treatment, and the slope of the linear regression curve of the separation rate relative to the G-force was outside the expected range. Furthermore, in the heat-shrinkable films of Comparative Examples 1 to 6, the fusion temperature was not measured after mixing with PET fragments and heat treatment.

[0168] Therefore, according to the present invention, the advantage is that no fusion products are formed after heat treatment; or even if fusion products are formed, recyclable samples can be distinguished by segmenting and quantifying them within the fused sample. Furthermore, the test results above show that the polyester heat-shrinkable film according to the present invention can be easily recycled under various heat treatment conditions.

Claims

1. A heat-shrinkable film comprising a copolyester resin, said copolyester resin comprising a diol component and a dicarboxylic acid component, in, When a mixture is prepared by (i) fragments obtained by cutting the heat-shrinkable film into squares with a side length of 10 mm or less, and (ii) fragments obtained by crushing polyethylene terephthalate (PET) containers to a particle size of 12.5 mm or less, in a weight ratio of 3:97, and the mixture is heat-treated at a temperature of 140°C to 210°C for 30 to 90 minutes, no fusion product is formed; or, when the fusion product is formed, the slope of the linear regression curve of the following separation rate (%) relative to G force (G) is 0.02% / G or greater when the fusion product is centrifuged; Separation rate (%) = [total weight of fragments separated from the fusion product during centrifugation (g) / weight of the initial fusion product (g)] × 100.

2. The heat-shrinkable film according to claim 1, wherein, After heat treatment of the fragment mixture, no fusion product is formed, or a fusion product with a particle size not exceeding twice the particle size of the PET container fragments is formed.

3. The heat-shrinkable film according to claim 1, wherein, The centrifugation was carried out under a force of 100 G to 650 G.

4. The heat-shrinkable film according to claim 1, wherein, When the fragment mixture is heat-treated at 140°C to 210°C for 30 to 90 minutes, and the temperature is increased from 20°C to 280°C at a rate of 10°C / min using differential scanning calorimetry (DSC) during the first scan, the melting temperature (T) is... m It occurs at temperatures 10°C or higher than the heat treatment temperature.

5. A heat-shrinkable film comprising a copolyester resin, said copolyester resin comprising a diol component and a dicarboxylic acid component, in, When a mixture is prepared by (i) fragments obtained by cutting heat-shrinkable film into squares with a side length of 10 mm or less, and (ii) fragments obtained by crushing polyethylene terephthalate (PET) containers to a particle size of 12.5 mm or less, at a weight ratio of 3:97, and the mixture is heat-treated at a temperature of 140°C to 210°C for 30 to 90 minutes, while the temperature is increased from 20°C to 280°C at a rate of 10°C / min using differential scanning calorimetry (DSC), and the melting temperature (T) is measured during the first scan, the melting temperature is determined. m It occurs at temperatures 10°C or higher than the heat treatment temperature.

6. The heat-shrinkable film according to claim 5, wherein, The melting temperature (T) in the first scan m The ΔH at this point is 0.1 J / g or greater.

7. The heat-shrinkable film according to claim 5, wherein, Following the first scan, during a second scan performed simultaneously using differential scanning calorimetry (DSC) to raise the temperature from 20°C to 280°C at a rate of 10°C / min, no melting temperature (T) was observed. m ).

8. The heat-shrinkable film according to claim 1 or 5, wherein, Under conditions of 95°C and 15 seconds, the heat-shrinkable film exhibits a shrinkage rate of 60% or higher in the main shrinkage direction.

9. The heat-shrinkable film according to claim 1 or 5, wherein, Under conditions of 85°C and 15 seconds, the heat-shrinkable film exhibits a shrinkage rate of 40% or higher in the main shrinkage direction.

10. The heat-shrinkable film according to claim 1 or 5, wherein the diol component is at least one selected from the group consisting of: bis(2-hydroxyethyl) terephthalate (BHET), isosorbide, neopentyl glycol, ethylene glycol, cyclohexanediol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2-methylene-1,3-propanediol, 2-ethyl-1,3-propanediol, 2-isopropyl -1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 1,4-butanediol, 2,3-butanediol, 3-methyl-1,5-pentanediol, 3-methyl-2,4-pentanediol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,4-cyclohexanediol, diethylene glycol, 4-(hydroxymethyl)cyclohexylmethyl-4-(hydroxymethyl)cyclohexanecarboxylate and 4-(4-(hydroxymethyl)cyclohexylmethoxymethyl)cyclohexylethanol.

11. The heat-shrinkable film according to claim 1 or 5, wherein, The dicarboxylic acid component is selected from at least one of the following groups: isophthalic acid, terephthalic acid, dimethyl isophthalate, phthalic acid, dimethyl phthalate, phthalic anhydride, 2,6-naphthalenedicarboxylic acid, dimethyl 2,6-naphthalenedicarboxylic acid, diphenyl dicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, dimethyl 1,4-cyclohexanedicarboxylic acid, dimethyl 1,3-cyclohexanedicarboxylic acid, sebacic acid, succinic acid, isodecylsuccinic acid, maleic acid, maleic anhydride, fumaric acid, adipic acid, glutaric acid, and azelaic acid.

12. The heat-shrinkable film according to claim 1 or 5, wherein the diol component and the dicarboxylic acid component comprise one or more types of recycled monomers.

13. The heat-shrinkable film according to claim 1 or 5, wherein, The copolyester resin contains at least one selected from the group consisting of antimony (Sb), titanium (Ti), zinc (Zn), germanium (Ge), magnesium (Mg) and manganese (Mn) as a polymerization catalyst.

14. The heat-shrinkable film according to claim 1 or 5, wherein, The film containing copolyester resin is uniaxially stretched at a stretch ratio of 1.5 to 6 times in the transverse direction or 1.05 to 6 times in the longitudinal direction.

15. The heat-shrinkable film according to claim 1 or 5, wherein, The film containing copolyester resin is biaxially stretched at a stretch ratio of 1.5 to 6 times in the transverse direction and 1.05 to 6 times in the longitudinal direction.

16. The heat-shrinkable film according to claim 1 or 5, wherein, The membrane containing copolyester resin is a single-layer membrane.

17. The heat-shrinkable film according to claim 1 or 5, wherein, A film containing copolyester resin is a multilayer film consisting of a base layer and a resin layer.

18. The heat-shrinkable film according to claim 1 or 5, wherein, A film containing a copolyester resin is prepared by the following steps: molding the polyester resin mixture to prepare an unstretched sheet; and stretching the unstretched sheet.